Start-up of full-scale two-stage upflow anaerobic sludge blanket (UASB) reactors treating distillery slops - Ghimire, Ashok B. (1999)
This study is an evaluation of the start-up performance of full-scale tow-stage upflow anaerobic sludge blanket (UASB) reactors, treating distillery slops of an alcohol distillery in the Philippines. Each stage consisted of three reactors. These reactors were inoculated with non-granular seed sludge acquired from an existing methane upflow reactors (MURs), treating slops of the same distillery. The reactor pH was stable and within range, i.e., 6.8-7.5. The temperature of the reactors was within the desired operating range of 35-38°C (mesophilic). There were no observed reactor upsets which could be attributed to sudden increase in volatile fatty acids (VFA) levels in the reactor contents, indicating that the system had sufficienct buffering capacity. The methane content of biogas was 57-62%. The produced biogas was used to generate power for the plant operations. An upflow velocity increment of 0.4 m for every day resulted in sludge washout, especially in second-stage reactors. Nevertheless after the re-addition of more seed sludge and nuclei to the reactors, and adjusting the upflow velocity increase to 0.5m for every 2-4 days, the sludge production and its retention in the reactors significantly improved with time. Sludge concentration varied over depth. It was higher in the lower sections of the reactors. The smaller and poorly-settling sludge developed in the lower depths of the reactors. As a result, more sludge with better settleability accumulated in the reactors.
the CODt removal efficiency of the reactors was widely varying. This could be attributed mainly to shock loadings caused by inconsistent COD concentration and volumetric flow rate of the influent, and insufficient quality of sludge. The first-stage reactors performed far better compared to the second-stage reactors were severely affected by highly varying concentration of the first-stage effluents. However, in the light of significant improvement in the sludge production and its accumulation in the reactors, it could be projected that the first stage reactors would reach the steady-state condition in about 220 days and the second-stage reactors in about 280 days as well. To conclude, the overall start-up performance of both first-and second-stage UASB reactors was satisfactory.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Sewage -- Purification -- Activated sludge process; Biochemical reactors; Distilling industries -- By-products.